Chromatin barcodes as biomarkers for melanoma. (27th May 2014) - Bastonini, Emanuela; Jeznach, Magdalena; Field, Megan; Juszczyk, Katarzyna; Corfield, Emily; Dezfouli, Mehrnoush; Ahmat, Nurfilza; Smith, Aimee; Womersley, Howard; Jordan, Philip; Ramadass, Aroul; Akoulitchev, Alexandre; et al.
Summary The major barrier to effective cancer therapy is the presence of genetic and phenotypic heterogeneity within cancer cell populations that provides a reservoir of therapeutically resistant cells. As the degree of heterogeneity present within tumours will be proportional to tumour burden, the development of rapid, robust, accurate and sensitive biomarkers for cancer progression that could detect clinically occult disease before substantial heterogeneity develops would provide a major therapeutic benefit. Here, we explore the application of chromatin conformation capture technology to generate a diagnostic epigenetic barcode for melanoma. The results indicate that binary states from chromatin conformations at 15 loci within five genes can be used to provide rapid, non‐invasive multivariate test for the presence of melanoma using as little as 200 μl of patient blood.